2012
DOI: 10.1002/pd.3830
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of non‐visualization of the fetal gallbladder and amniotic fluid digestive enzymes analysis to outcome

Abstract: Non-visualization of the fetal gallbladder was associated with severe anomalies in 24% of cases. Prior to 22 weeks, determination of AF-DE contributes to the prediction of biliary atresia or the presence of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 21 publications
5
39
1
1
Order By: Relevance
“…The sensitivity and specificity of abnormal GGTP in predicting serious morbidity in fetuses whose gallbladder was not visualized was 80 and 96%, respectively. These findings concur with those of Dreux et al [6] who concluded that prior to 22 weeks of gestation, an abnormal pattern of amniotic fluid digestive enzymes had 90% sensitivity and 80% specificity in detecting CF or BA; however, after 22 weeks, the sensitivity dropped to 53%. In contrast, Shen et al [7] concluded that testing digestive enzymes in amniotic fluid is not justified for assessing cases of isolated NVFGB.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The sensitivity and specificity of abnormal GGTP in predicting serious morbidity in fetuses whose gallbladder was not visualized was 80 and 96%, respectively. These findings concur with those of Dreux et al [6] who concluded that prior to 22 weeks of gestation, an abnormal pattern of amniotic fluid digestive enzymes had 90% sensitivity and 80% specificity in detecting CF or BA; however, after 22 weeks, the sensitivity dropped to 53%. In contrast, Shen et al [7] concluded that testing digestive enzymes in amniotic fluid is not justified for assessing cases of isolated NVFGB.…”
Section: Discussionsupporting
confidence: 56%
“…Amniotic fluid digestive enzymes are considered by some as a valuable prenatal tool to assess the fetal bile apparatus [6,12,14,18]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations